2021
DOI: 10.1038/s41374-020-00520-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and graft-versus-host disease: a tale of two diseases (and why age matters)

Abstract: Disorders involving injury to tissue stem cells that ensure normal tissue homeostasis and repair have potential to show unusually devastating clinical consequences. Acute graft-versus-host disease (aGVHD) is one condition where relatively few cytotoxic immune cells target skin stem cells to produce significant morbidity and mortality. By analogy, SARS-CoV-2 is a vector that initially homes to pulmonary stem cells that preferentially express the ACE2 receptor, thus potentially incurring similarly robust patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Galimberti et al reported that COVID-19 is characterized by a cytokine storm and hyperactivation of the immune response, similar to that observed with acute GVHD, resulting in damage to various organs [ 15 ]. Murphy reported that in both acute GVHD and COVID-19, critical epithelial stem cell populations are preferentially targeted in the early phases of the disease [ 16 ]. Furthermore, both conditions are mediated, in part, by cytokines, with a cytokine storm playing an important role in further driving and amplifying the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Galimberti et al reported that COVID-19 is characterized by a cytokine storm and hyperactivation of the immune response, similar to that observed with acute GVHD, resulting in damage to various organs [ 15 ]. Murphy reported that in both acute GVHD and COVID-19, critical epithelial stem cell populations are preferentially targeted in the early phases of the disease [ 16 ]. Furthermore, both conditions are mediated, in part, by cytokines, with a cytokine storm playing an important role in further driving and amplifying the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent endovasculitis has also been observed ( 123 ). In patients suffering from GVH disease, lung histological lesions are characterized by alveolar changes (intra-alveolar fibrin, organizing pneumonia, and chronic interstitial pneumonia), atypical pneumocytes, intra-epithelial bronchiolar T cells, and perivenular cuffing ( 124 127 ).…”
Section: Pathological Similarities Between Transplanted Patients and Covid-19 Patients: Tissues Injured With Picture Of Chronic Vascular mentioning
confidence: 99%